Guideline-level monitoring, biomarker levels and pharmacological treatment in migrants and native Danes with type 2 diabetes: Population-wide analyses. - Anders Aasted Isaksen; Annelli Sandbæk; Mette Vinther Skriver; Gregers Stig Andersen; Lasse Bjerg (Public Library of Science (PLoS), 2023)
The prevalence of type 2 diabetes (T2D) is higher in migrants compared to native populations in many countries, but the evidence on disparities in T2D care in migrants is inconsistent. Therefore, this study aimed to examine this in Denmark. In a cross-sectional, register-based study on 254,097 individuals with T2D, 11 indicators of guideline-level care were analysed: a) monitoring: hemoglobin-A1c (HbA1c), low-density lipoprotein cholesterol (LDL-C), screening for diabetic nephropathy, retinopathy, and foot disease, b) biomarker control: HbA1c and LDL-C levels, and c) pharmacological treatment: glucose-lowering drugs (GLD), lipid-lowering drugs, angiotensin-converting enzyme-inhibitors/angiotensin receptor blockers, and antiplatelet therapy. Migrants were grouped by countries of origin: Middle East, Europe, Turkey, Former Yugoslavia, Pakistan, Sri Lanka, Somalia, Vietnam. In all migrant groups except the Europe-group, T2D was more prevalent than in native Danes (crude relative risk (RR) from 0.62 [0.61-0.64] (Europe) to 3.98 [3.82-4.14] (Sri Lanka)). In eight indicators, non-fulfillment was common (>25% among native Danes). Apart from monitoring in the Sri Lanka-group, migrants were at similar or higher risk of non-fulfillment than native Danes across all indicators of monitoring and biomarker control (RR from 0.64 [0.51-0.80] (HbA1c monitoring, Sri Lanka) to 1.78 [1.67-1.90] (LDL-C control, Somalia)), while no overall pattern was observed for pharmacological treatment (RR from 0.61 [0.46-0.80] (GLD, Sri Lanka) to 1.67 [1.34-2.09] (GLD, Somalia)). Care was poorest in migrants from Somalia, who had increased risk in all eleven indicators, and the highest risk in nine. Adjusted risks were elevated in some migrant groups, particularly in indicators of biomarker control (fully-adjusted RR from 0.84 [0.75-0.94] (LDL-C levels, Vietnam) to 1.44 [1.35-1.54] (LDL-C levels, Somalia)). In most migrant groups, T2D was more prevalent, and monitoring and biomarker control was inferior compared to native Danes. Migrants from Somalia received the poorest care overall, and had exceedingly high lipid levels.